Budaya Organisasi dalam Pelayanan Publik di Kecamatan Suwawa, Kabupaten Bone Bolango - Nur Fidya Podungge; Yanti Aneta; Raihan Hanasi (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
A company's or organization's identity and operational style are shaped by a variety of factors that are collectively referred to as its organizational culture. By examining particular elements innovation, attention to detail, outcome orientation, people orientation, and team orientation this study seeks to investigate the organizational culture within public services in Suwawa District, Bone Bolango Regency. A triangulation model and a descriptive approach were used in the qualitative method. The results show that Suwawa District's implementation of public service organizational culture is generally successful, although each component has unique strengths and weaknesses: innovation uses technology but is limited by facility and human resource constraints; attention to detail is maximized through careful document verification; outcome orientation is highly effective, aligning with established standards and the Public Satisfaction Index; people orientation addresses staff welfare but lacks support from planned human resource development; and team orientation works in concert but needs to be strengthened to ensure consistency and prevent the influence of sectoral egos.